Current guidelines for the management of Lyme borreliosis in European countries - Wyleciał, Zuzanna; Ząber, Julia; Zamachowska, Wiktoria (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Lyme borreliosis, caused by Borrelia burgdorferi sensu lato complex, is the most common vector-borne disease in Europe. Transmitted by Ixodes ticks, its prevalence is increasing due to climate change, expanded tick habitats, and improved diagnostic awareness. Consequently, unified and evidence-based management guidelines are critical to ensure consistent diagnosis and treatment across European countries. This article provides an overview of current guidelines from 2023 for the management of Lyme borreliosis in Europe. Materials and methods: A literature search was conducted by analysing scientific articles published in Google Scholar, PubMed, and UpToDate using keywords included: Lyme disease; guidelines; Borrelia burgdorferi; management. We also searched current guidelines of Polish Society of Epidemiology and Infectious Diseases and recommendations from other European countries. Description of the state of knowledge: There are 3 stages of Lyme disease: early localized, early disseminated and late. Clinical diagnosis is based on symptoms, history of tick exposure, and observation of erythema migrans. To confirm Lyme disease, laboratory tests must also be performed. Lyme borreliosis is typically treated with antibiotics depending on the character. Conclusion: European guidelines for Lyme borreliosis emphasize early diagnosis and appropriate antibiotic therapy based on disease stage. Preventive measures and public health initiatives are essential to reduce the disease burden. While current guidelines ensure effective management, continued harmonization and advancements in diagnostics, treatment, and vaccine development will further enhance Lyme borreliosis care across Europe. Keywords: Lyme disease; guidelines; Borrelia burgdorferi; management.